Caderno de leitura de poemas de Tobias Barreto - Oliveira, Noeme Leite do Nascimento (2021)
This thesis for the Professional Master’s Degree in Languages aims to develop a intervention proposal in the literary reading of some poems, from the book Dias e Noites, by Tobias Barreto, in order to stimulate the reception of texts with romantic love themes and Condoreism Poetry of this writer, instigating the identification of irony and intertextualities of his poetry in order to form literary readers who value the process of subjective reception based on their personal experiences and the horizon of expectation of these poems. This thesis proposes the production of a reading workbook aimed for the final grades of the Elementary School. In the first part of this thesis, we present discussions about the challenges of teaching literature and reading poems from the characteristics of the lyrical genre. In the second part, we will go deeper into the debate about the reader’s identification with the reading of poems from the conceptions of lyric literacy and subjective reading. The third part consists of the intervention workbook with its practical parts built from scripts of literary reading, aesthetics, deciphering the riddles of women, childhood and social criticism, as well as dialogues with the different arts and a contextualization with the present. In these three parts we will debate the specifics of the lyrical genre, as well as the importance of developing political awareness, identification with the readings and the collaborative and transforming profile of readers facing experiences with the practice of reading. Methodologically, the interdisciplinary conceptions of a reader’s identification will be used as a theoretical basis, following the exploration of the stages of literacy by Rildo Cosson, the exploration of the perspectives of subjective reading by Annie Rouxel, the approaches aimed at reading the poetic text proposed by Hélder Pinheiro and the reader’s cultural identification process, articulated by Carlos Gomes. As a final product, the reading workbook is composed of activities that explore the subjectivity of the reader and his identification process with the readings of Tobias Barreto’s poetry, based on the wordplay and ironies identified in the riddles, in the representation of love, of the woman and patriotism.